Thermohaline conditions and circulation in the Gulf of Thailand during the northeast monsoon. (1st August 2021) - Guo, Jingsong; Qu, Dapeng; Zhang, Zhixin; Sangmanee, Chalermrat; Chanthasiri, Nuttida; Guo, Binghuo
Abstract: Hydrographic data from the Gulf of Thailand (GoT) reveal two bottom saline water areas (BSWA1 and BSWA2) with salinity (S) ≥ 33.0 psu and where the water columns are highly stratified during December–January. Observational results from a seafloor acoustic doppler current profiler verify that the current is mainly dominated by a barotropic current. The monthly average sea-level-anomaly (SLA) and barotropic current vector maps confirm a cyclonic circulation in the northern GoT during November–January. The BSWA1 is located near the center of the cyclonic circulation. The BSWA1 and cyclonic circulation simultaneously enter their weakening phases, which suggests that the cyclonic circulation convergence plays a key role in maintaining the BSWA1. The BSWA2 occurs as a narrow strip concentrated along the eastern slope of the basin in the southern GoT during December–January. The southern GoT also has higher SLA and forms a congregation area of diluted water with S < 31.0 psu that enters from the north and south of this region during December–January. Highlights: There remain two bottom saline water of S ≥ 33.0 psu in the GoT during winter where water columns are highly stratified. Observational current profiles in December 2018 verify that the current is dominated by different part depending on wind. Cyclonic circulation in the northern GoT during winter plays a key role in the formation and maintenance of the BSWA1.